Psychology : from inquiry to understanding - Lilienfeld, Scott O., 1960- (Boston : Pearson/Allyn Bacon, 2009)
A focus on How to Think, not merely What to Think!
Prologue: How Psychology Became a Science 1: Science and Pseudoscience in Psychology: Skills for Thinking Scientifically in Everyday Life 2: Research Methods: Safeguards against Error 3: Cross-Cultural Psychology: How Culture Affects Us 4: Biological Psychology: The Brain Body Communication Superhighway 5: Sensation and Perception: How We Sense and Conceptualise the World 6: Consciousness: Expanding the Boundaries of Psychological Inquiry 7: Learning: How Nurture Changes Us 8: Memory: Constructing and Reconstructing Our Pasts 9: Language, Thinking and Reasoning: Getting Inside Our Talking Heads 10: Intelligence and IQ Testing: Controversy and Consensus 11: Human Development: How and Why We Change 12: Emotion and Motivation: What Moves Us 13: Stress, Coping and Health: The Mind Body Interconnection 14: Social Psychology: How Others Affect Us 15: Personality: Who We Are 16: Psychological Disorders: When Adaptation Breaks Down 17: Psychological and Biological Treatments: Helping People Change.
Includes bibliographical references and indexes.
Keywords: Psychology